Comparative Analysis of Measured Tidal Data with Tidal Data from Forecasting (Case Study of Tanjung Priok Tidal Station) - Dinaryoko, Arif; Zakaria, Ahmad; Tugiono, Subuh (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
AbstractThis research was conducted to study the tidal characteristics. The data used in this study are the hourly tide data measured in the field and the tidal data from the BIG with data length from 1985 to 1989 at the Tanjung Priok tidal station, Jakarta Province, Indonesia. This modeling is carried out using a data length of 30 days for a data term of 720. By using the observational data and applying it in the Anfor program which uses the least squares method, produces a tidal periodic model that is obtained using 9 tidal harmonic components. From the results of modeling and measured data it can be seen the correlation coefficient. Based on these results, it can be concluded that the measured tide data components with the BIG tide data components are similar. The average correlation coefficient between the two data sets was 0.9644. From this research it can be seen that the value of the tidal data is said to be very good. Keywords: daily tides, correlation coefficient